The Development of Green Chemistry Teaching Material Based on Organic Compound Synthesis - Annisa Mustika Pertiwi; Deana Wahyuningrum (Universitas Sultan Ageng Tirtayasa, 2024)
Green chemistry is currently included in 10th-grade chemistry in Indonesia's Merdeka curriculum. However, the learning implementation is still limited to the knowledge of approximately 12 principles of green chemistry, but its relevance to real-world applications is less discussed. The process of organic compound synthesis is a problem that is closely related to the application of green chemistry. This research aims to produce context-based green chemistry teaching materials for senior high school students on the basis of experiments using an ionic liquid and microwave-assisted organic synthesis (MAOS) method in the synthesis of an organic compound named dehydrozingerone (DHZ) from vanillin and acetone. The instructional material development method follows the Research & Development (RnD) method via a 4D model and includes the Define, Design, Develop, and Deliver stages. The guided-inquiry student worksheets developed in this research were tested in a classroom setting with 31 10th grade students from Al Ma'soem Senior High School in Bandung, West Java, Indonesia. The evaluation of the teaching materials received a positive response from the students, with a score of 78.29%, indicating a "good" classification. The findings of this study highlight the potential of these contextual teaching materials to enhance students' engagement and understanding in learning green chemistry concepts and applications.